Inhibition of Mycobacterium tuberculosis Transaminase BioA by Aryl Hydrazines and Hydrazides. Issue 4 (31st January 2014) - Dai, Ran; Wilson, Daniel J.; Geders, Todd W.; Aldrich, Courtney C.; Finzel, Barry C.
Abstract 7, 8‐Diaminopelargonic acid synthase (BioA) of Mycobacterium tuberculosis is a recently validated target for therapeutic intervention in the treatment of tuberculosis (TB). Using biophysical fragment screening and structural characterization of compounds, we have identified a potent aryl hydrazine inhibitor of BioA that reversibly modifies the pyridoxal‐5′‐phosphate (PLP) cofactor, forming a stable quinonoid. Analogous hydrazides also form covalent adducts that can be observed crystallographically but are incapable of inactivating the enzyme. In the X‐ray crystal structures, small molecules induce unexpected conformational remodeling in the substrate binding site. We compared these conformational changes to those induced upon binding of the substrate (7‐keto‐8‐aminopelargonic acid), and characterized the inhibition kinetics and the X‐ray crystal structures of BioA with the hydrazine compound and analogues to unveil the mechanism of this reversible covalent modification.